Measurement of Reliability of Test Instruments Through Management of Education and Psychology - Royadi, Dedi; Mohd Nawi, Mohd Nasrun; Supyaningsih​, Fitria (APTISI Transactions on Management (ATM), 2018)
At this time in the world of work or in job management workers are required to be able to solve problems that mean that in education and psychology management must be able to build or develop instruments in all fields of management. The development of measurement instruments in the field of psychology and education many assume the use of unidimensional measurements, which conceptually formulated that there is one type of ability factor, personality, character, and attitude measured by one measurement instrument. This study aims to allow readers to understand the notions of reliability, reliability of learning outcomes tests, general models of reliability, simple methods of estimating reliability, retesting methods, parallel methods, halves, moment product equations, Flanagan equations, Rulon equations, reliability coefficients , and standard measurement errors. In order for this management research to take place smoothly, the researcher uses the literature study method as his research method. Keywords: Educational management, Measurement Instruments, Reliability